Integration of Personalized Service Delivery with Information Technology : Future of CRM in Indian Banking - Bagla, Ramesh Kumar; Singh, Anurupa B. (Prabandhan: Indian Journal of Management, 2016)
This study aimed to critically review the state of customer relationship management (CRM) in Indian banks on the basis of secondary data, information available, and our own experiences both as customers and a banker [first author of the paper has an experience of 17 years in the Banking sector]. With the advent of professionally managed private sector banks in India in 1993, the focus of CRM has shifted from personal relationship to technology driven module based relationship management with minimal personal touch. Notwithstanding all the noise about implementation of ambitious CRM plans by Indian banks, they have not been able to impress customers because of cross selling overdrive at the cost of customer delight. There is an urgent need to integrate information technology enabled solutions using big data analytics with tailor made personalized relationship management for which an integrated CRM Model has been proposed in this paper.